Cote d'Ivoire : Competitiveness, Cocoa, And The Real Exchange Rate - Bogetić, Željko 1993- (The World Bank, 2007)
This paper explores competitiveness of Cote d'Ivoire's economy over a long period of 1960-2003 and its link with cocoa prices. The main conclusions are as follows. First, using four measures of real effective exchange rate (REER) for the 1960-2002 period, we track the evolution of REER and conclude, inter alia, that until 2003, REER remained well below its 1994 level. Second, we find that based on our measure of the multilateral REER with dynamic weights, which covers most recorded trade, France no longer dominates Cote d'Ivoire's trade. Instead, Cote d'Ivoire has diversified its set of trading partners. Unfortunately, it has also specialized in one export product, raw cocoa. This paper aims to contribute to the question to what extent do cocoa prices affect Cote d'Ivoire's competitiveness in world trade? Third, the answer to this question is that cocoa prices are an important determinant of Cote d'Ivoire's competitiveness. Similar to the case of a classic "Dutch Disease," increases in the real world price of a "natural resource" (i.e., cocoa) tend to result in the appreciation of the CFA franc and a loss in competitiveness. Econometric tests further confirm that 1994 was a "break-point" not only for growth and productivity (as documented in the two related papers) but also for trade competitiveness. Recent productivity per worker trends versus wages also seem to indicate slow growth in 1996-2000, without major improvement in competitiveness